2021
DOI: 10.1111/tpj.15489
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms and hormonal regulation underpinning morphological dormancy: a case study using Apium graveolens (Apiaceae)

Abstract: Underdeveloped (small) embryos embedded in abundant endosperm tissue, and thus having morphological dormancy (MD) or morphophysiological dormancy (MPD), are considered to be the ancestral state in seed dormancy evolution. This trait is retained in the Apiaceae family, which provides excellent model systems for investigating the underpinning mechanisms. We investigated Apium graveolens (celery) MD by combined innovative imaging and embryo growth assays with the quantification of hormone metabolism, as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 89 publications
(198 reference statements)
2
14
0
Order By: Relevance
“…In addition, the absolute ABA content was much higher than the absolute GA3 content and the ABA/GA3 ratio showed a similar trend to ABA content (Figure 1B-E). These findings are consistent with those in the seeds of red bayberry [29], celery [30], and ginkgo [31]. Simultaneously, the expression patterns of several ABA and GA biosynthesis and deactivation genes, including SDRs, CYP707As, KO, KAO, and GA20oxs, exhibited high correlations with the changes in ABA and GA3 levels (Figure 4A).…”
Section: Metabolism and Regulation Of Plant Hormones In Callery Pear ...supporting
confidence: 86%
“…In addition, the absolute ABA content was much higher than the absolute GA3 content and the ABA/GA3 ratio showed a similar trend to ABA content (Figure 1B-E). These findings are consistent with those in the seeds of red bayberry [29], celery [30], and ginkgo [31]. Simultaneously, the expression patterns of several ABA and GA biosynthesis and deactivation genes, including SDRs, CYP707As, KO, KAO, and GA20oxs, exhibited high correlations with the changes in ABA and GA3 levels (Figure 4A).…”
Section: Metabolism and Regulation Of Plant Hormones In Callery Pear ...supporting
confidence: 86%
“…ABA levels are closely related to seed dormancy status. In this study, ABA levels showed a significant decline during the germination process ( Figure 2 ), which was similar to that of red bayberry [ 15 ], celery [ 16 ], ginkgo [ 17 ], and pear [ 18 ]. Concomitantly, the expression profiles of multiple ABA biosynthesis and deactivation genes, including NCEDs and CYP707As, were highly consistent with the dynamics of ABA ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 71%
“…Dormancy is an evolved trait of perennial plants that allows vegetative buds to survive harsh environmental conditions, and it was classified into three categories by Lang (1987): ecodormancy, caused by limitations in environmental factors; endodormancy, where the inhibition resides in the dormant structure itself, and paradormancy, inhibited by distal organs. Abscisic acid (ABA) is recognized as an essential phytohormone in dormancy regulation, especially as a central hub in seed dormancy [1][2][3][4], but its regulatory mechanism in bud dormancy is not well understood.…”
Section: Introductionmentioning
confidence: 99%